ChemInform Abstract: Synthesis, Characterization, and Evaluation of Radiometal‐Containing Peptide Nucleic Acids. Issue 25 (5th June 2015) - Stephan, Holger; Foerster, Christian; Gasser, Gilles
Abstract: Review: 67 refs.